Think Aloud Testing in Usability Evaluation of the Love Your Breast Application to Enhance Self-Examination Behavior in Adolescents - Anggraini, Dian; Rifayanti, Lidya (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Adolescents are a key demographic for promoting early breast cancer detection through Self-Breast Examination (SADARI). Mobile health (mHealth) applications offer potential to increase awareness and encourage preventive behaviors, but their effectiveness depends on usability and user experience. Objective: This study aimed to evaluate the usability of the Love Your Breast mobile application using the Think Aloud method and to identify design improvements to enhance its effectiveness for adolescent users. Methods: A descriptive qualitative design was employed. Ten female high school students in Bandung participated in Think Aloud usability testing, performing seven task scenarios while verbalizing their thoughts. Quantitative data were analyzed through task success rate calculations, while qualitative data were examined using thematic analysis. Results: The application achieved an average success rate of 86%. Thematic analysis revealed three main usability themes: (1) general observation—issues with font size, color brightness, and background images; (2) performance expectancy—users could not access the video feature; and (3) effort expectancy—some users experienced slow downloads due to poor internet access. Although the app was considered informative and easy to use, these issues negatively affected the overall user experience. Conclusion: The Love Your Breast app shows promise as a tool for adolescent breast cancer awareness and early detection. Future updates should address visual consistency, enable offline video access, and improve performance under limited connectivity. These changes will enhance usability and align with user-centered mHealth design principles, supporting its broader adoption in adolescent health promotion.